THE ROLE OF SOCIAL MEDIA IN BUILDING BRAND IMAGE IN THE DIGITAL ERA - Rifqi Lathifa, Faurina; Mar’atul Juleha, Fitria (Politeknik Negeri Madiun, 2023)
Social media has become a vital platform for communication and marketing in the digital era. This article aims to review and analyze the role of social media in shaping brand image, emphasizing how interaction, engagement, and digital storytelling influence consumer perception. Using a literature review approach, this study examines previous research related to marketing communication, consumer engagement, and brand authenticity. The findings reveal that social media plays a significant role in building and maintaining brand image through two-way communication, viral content, and online community participation. In conclusion, social media enables brands to create strong emotional connections with consumers and enhances brand trust through authenticity and consistent value communication